2017
DOI: 10.1038/leu.2017.137
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-146a reduces MHC-II expression via targeting JAK/STAT signaling in dendritic cells after stem cell transplantation

Abstract: Acute Graft-versus-host disease (GVHD) is a major immunological complication after allogeneic hematopoietic cell transplantation and a better understanding of the molecular regulation of the disease could help to develop novel targeted therapies. Here we found that a G/C polymorphism within the human microRNA-146a (miR-146a) gene of transplant-recipients, which causes reduced miR-146a levels, was strongly associated with the risk of developing severe acute GVHD (n=289). In mice, deficiency of miR-146a in the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 26 publications
4
67
0
Order By: Relevance
“…Multiple miRs in sera were strongly connected to acute GVHD risk 73 , in particular miR-155 and miR146a 74 . In initial studies, the presence of a miR-146a polymorphism (rs2910164) in the donor or the allo- hematopoietic cell transplant recipient was connected to higher rates of grade III and IV acute GVHD 75,76 , a finding requiring confirmation in larger patient cohorts. These and possibly other yet to be discovered biomarker panels hold promise to better predict the risk of acute GVHD and acute GVHD-related mortality, which could lead to a more individualized GVHD-prophylaxis approach.…”
Section: Biomarkers For Agvhd Severity - Studies In Patientsmentioning
confidence: 99%
“…Multiple miRs in sera were strongly connected to acute GVHD risk 73 , in particular miR-155 and miR146a 74 . In initial studies, the presence of a miR-146a polymorphism (rs2910164) in the donor or the allo- hematopoietic cell transplant recipient was connected to higher rates of grade III and IV acute GVHD 75,76 , a finding requiring confirmation in larger patient cohorts. These and possibly other yet to be discovered biomarker panels hold promise to better predict the risk of acute GVHD and acute GVHD-related mortality, which could lead to a more individualized GVHD-prophylaxis approach.…”
Section: Biomarkers For Agvhd Severity - Studies In Patientsmentioning
confidence: 99%
“…Besides soluble factors in the blood of the GVHD patients, micro‐RNAs, which determine the transcription of multiple target genes were evaluated after allo‐HSCT [reviewed in (Zeiser & Blazar, )]. Functional studies in preclinical models showed that several miRs promoted or inhibited GVHD, such as miR‐155 (Ranganathan et al , ; Chen et al , ), miR100 (Leonhardt et al , ), miR‐146a (Stickel et al , ; Stickel et al , ). The pro‐inflammatory miR‐155 was required for CXCR4‐dependent donor T‐cell migration (Ranganathan et al , ) and NLRP3 inflammasome activation in dendritic cells (Chen et al , ).…”
Section: Costimulatory Pathways Chemokines and Cytokines In Acute Gvhdmentioning
confidence: 99%
“…Preclinical studies showed that JAK1/2 inhibition had also a profound effect on DCs and neutrophils in the setting of acute GVHD. JAK1/2 blockade reduced expression of the transcription factor CIITA which activates the MHC class II promoter in DCs (Stickel et al , ) and reduced the migration of recipient neutrophils from the ileum to mesenteric lymph nodes (Hülsdünker et al , ). In May 2019, the JAK1/2 inhibitor ruxolitinib was approved by the US Food and Drug Administration (FDA) for the treatment of acute steroid‐refractory GVHD (FDA, ) based on an open‐label, single‐arm, multicentre study (NCT02953678) of ruxolitinib that enrolled patients with steroid‐refractory acute GVHD grades 2 to 4.…”
Section: Kinase Inhibitors and Outlookmentioning
confidence: 99%
“…In vitro and in vivo analyses have shown that ruxolitinib affects several aspects of immune function related to GVHD, including inhibiting antigen-presenting cell function through inhibition of DC differentiation, reducing DC migratory capacity [33], decreasing DC expression of major histocompatibility complex class II [34], reducing T-cell proliferation and activation and decreasing cytokine production [35]. Furthermore, ruxolitinib treatment in murine models of GVHD was associated with the amelioration of disease manifestations and symptoms.…”
Section: Overview Of Ruxolitinib and Rationale For Targeting Jak Signalmentioning
confidence: 99%